2020
DOI: 10.3390/polym12030713
|View full text |Cite
|
Sign up to set email alerts
|

The Piezoresistive Highly Elastic Sensor Based on Carbon Nanotubes for the Detection of Breath

Abstract: Wearable electronic sensor was prepared on a light and flexible substrate. The breathing sensor has a broad assumption and great potential for portable devices in wearable technology. In the present work, the application of a flexible thermoplastic polyurethane/multiwalled carbon nanotubes (TPU/MWCNTs) strain sensor was demonstrated. This composite was prepared by a novel technique using a thermoplastic filtering membrane based on electrospinning technology. Aqueous dispersion of MWCNTs was filtered through me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 16 publications
0
14
0
1
Order By: Relevance
“…This is explained by the intrinsic piezoresistivity of CNTs [13,14], the contact conductive mechanism between CNTs and the tunneling effect that takes place between adjacent nanotubes. The combination of these factors leads to an enhanced strain sensitivity, much higher than those achieved for conventional metallic gauges [15][16][17][18][19].There are several studies of materials manufactured by 3D printing with CNTs as conductive fillers. Some specific examples are described below.…”
mentioning
confidence: 99%
“…This is explained by the intrinsic piezoresistivity of CNTs [13,14], the contact conductive mechanism between CNTs and the tunneling effect that takes place between adjacent nanotubes. The combination of these factors leads to an enhanced strain sensitivity, much higher than those achieved for conventional metallic gauges [15][16][17][18][19].There are several studies of materials manufactured by 3D printing with CNTs as conductive fillers. Some specific examples are described below.…”
mentioning
confidence: 99%
“…The advantages of using MWCNTs instead of pure ones lie in the additional advantages of the processed materials added to the composites. Scientists have tried different mixed kinds of polymers and nanoparticles to enhance the quality of MWCNT nanocomposite-based sensors [ 102 , 103 , 104 ]. These sensors have proven to have higher sensitivities in terms of G.F., lower response time, and lower hysteresis.…”
Section: Multi-walled Carbon Nanotube (Mwcnt)-based Strain Sensorsmentioning
confidence: 99%
“…Also, in [81], R. Danovà et al presented a new piezoresistive sensor for healthcare applications based on thermoplastic polyurethane (TPU) substrate and multi-walled carbon nanotubes (MWCNTs) active material; the resulting sensor was integrated on a T-shirt, protected by a thin silicon layer (Figure 6a). The research demonstrated the improvement in the sensitivity of the piezoresistive MWCNTs layers when these are oxidated by potassium permanganate (KMnO 4 ).…”
Section: Overview Of Smart Piezoresistive Textiles and Materials Used To Monitor Respiration Ratementioning
confidence: 99%